2015 International Conference on Advances in Computer Engineering and Applications 2015
DOI: 10.1109/icacea.2015.7164742
|View full text |Cite
|
Sign up to set email alerts
|

Finding experts in community question answering services: A theme based query likelihood language approach

Abstract: Community question answering services provide an open platform for users to acquire and share their knowledge. In the last decade, popularity of such services has increased noticeably. Large number of unanswered questions is a major problem for the growth of such services. A common way to address this issue is to route a new question to some selected users who have the potentiality in answering the question. Expert finding is the process of selecting such potential answerers. In this article, we have introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…(Yi and Godavarthy, 2014) proposed a predictive language model to solve the future expert finding problem. Their method probabilistically estimates the association between a candidate e and a topic m in a future time t 2 ; while the method described in (Momtazi and Naumann, 2013) estimates the mentioned probability according to their association in current time t 1 . (Srba et al, 2015) employ a probability model based on latent topics identified by LDA for the expertise estimation employed in QAbased approaches with non-QA sources of data to estimate users' knowledge early and more accurately for users with low levels of QA activity.…”
Section: Topic Modelsmentioning
confidence: 99%
“…(Yi and Godavarthy, 2014) proposed a predictive language model to solve the future expert finding problem. Their method probabilistically estimates the association between a candidate e and a topic m in a future time t 2 ; while the method described in (Momtazi and Naumann, 2013) estimates the mentioned probability according to their association in current time t 1 . (Srba et al, 2015) employ a probability model based on latent topics identified by LDA for the expertise estimation employed in QAbased approaches with non-QA sources of data to estimate users' knowledge early and more accurately for users with low levels of QA activity.…”
Section: Topic Modelsmentioning
confidence: 99%
“…The results showed that statistical topic models can be regarded as a suitable alternative for expert recommendation. Mandal et al [6] introduced a method using the theme in query likelihood language model for expert finding. In this case, the theme of the query was based on the parts of speech (POS) of the words in the query.…”
Section: Related Workmentioning
confidence: 99%